Penerapan Aplikasi Web Untuk Inventori Gudang Di Zakir Konveksi Indramayu - romanuddin, ahmad; pranoto, gatot tri; hadikristanto, wahyu (Peneliti.net, 2023)
This study aims to implement the availability of goods in warehouse inventory. This application was created to simplify the process of monitoring and managing inventory in warehouses, so as to increase efficiency and prevent shortages or excess stocks. The method used in this research is a case study method conducted at a retail company in Indramayu. Data were obtained through interviews and direct observation of inventory conditions at that time. The results of the study indicate that the implementation of the goods availability application is very helpful in monitoring and controlling the stock of goods in the warehouse. By using this application, management can more easily track the incoming and outgoing goods, generate inventory reports automatically, and provide notifications when a product has reached the minimum stock limit. It is hoped that by implementing the application of the availability of goods in warehouse inventory, it can maintain inventory stability and improve work efficiency in this retail business.